An ultra-thin, low-resistance conductive polymer film and a method for preparing the same

By using ultra-thin, low-resistance conductive polymer films, combined with vacuum sputtering and electroplating technology, or zinc powder replacement reaction, the problems of complex production process, high cost and poor rigidity of the negative electrode copper foil of lithium battery are solved, and thinner , impact-resistant copper foil improves the safety and energy density of the battery.

CN117343429BActive Publication Date: 2025-02-18QINGDAO ZHONGKEHUALIAN ADVANCED MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311270985.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-01-09
Filing Date
2023-09-28
Publication Date
2025-02-18
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The production process of existing lithium battery negative electrode copper foil is complex and has high cost. The thickness of the copper foil is limited, and its rigidity and puncture resistance are poor, which can easily lead to battery short circuit.

Method used

Using ultra-thin, low resistance conductive polymer film, after mixing the polymer with the conductive substance and extruding it into a film, vacuum sputtering the conductive material to form an initial conductive layer, and then thickening the conductive layer by electroplating, or using zinc powder to replace it. The reaction forms a conductive layer.

Benefits of technology

The cumbersomeness and cost of the copper foil production process are reduced, and the copper foil is thinner and has the impact resistance of polymers, which improves the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005156765330000171
    Figure GDA0005156765330000171
Patent Text Reader

Abstract

The present invention provides an ultra-thin, low-resistance conductive polymer film and a preparation method thereof, belonging to the technical field of lithium-ion batteries. The diaphragm film has a thickness of 2-5 μm, no permeable pores, and a mass resistivity of ≤0.17 Ω*g / m 2 , tensile strength ≥ 100Mpa, elongation at room temperature ≥ 2.5%, elongation at high temperature ≥ 5%, smooth surface roughness (RA) ≤ 0.4μm, smooth surface roughness (RZ) ≤ 1μm, matte surface roughness (RA) ≤ 0.7μm, matte surface roughness (RZ) ≤ 1.5μm. The preparation method is: blending a polymer and an additive to form a blend, extruding and stretching it into a film, and then electroplating it through a copper sulfate solution to further grow copper on the film, that is, preferably adding a conductive material to the blend. The method of the present invention reduces the cumbersomeness and cost of the copper foil preparation process, and the prepared copper foil is thinner and lighter, while reducing the battery energy density, giving the copper foil the impact resistance of the polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to an ultra-thin, low-resistance conductive polymer film and a preparation method thereof. Background Art

[0002] At present, the lithium battery market has an increasingly urgent demand for high volume energy density and mass energy density. The positive and negative electrodes, electrolyte, and battery shell occupy most of the mass of the battery. The main material of the negative electrode current collector of lithium batteries is copper. Metal materials not only affect the volume energy density of the battery, but also the mass energy density of the battery. For the negative electrode copper foil of lithium batteries, the domestic market currently mostly uses roller cathodes and insoluble anodes to produce electrolytic copper foil in a continuous process. The thinner the copper foil, the less copper is used per unit battery, which is more conducive to reducing battery costs.

[0003] Traditional copper foil is composed of 99.5% pure copper. According to its thickness, it can be divided into ultra-thin copper foil (≤6μm), ultra-thin copper foil (6-12μm), thin copper foil (12-18μm), conventional copper foil (18-70μm), thick copper foil (≥70μm), etc. Its characteristics are heavy weight per unit area, high usage of metal copper material, and high thermal conductivity.

[0004] The subsequent production process of copper foil also requires steps such as raw foil, pickling, water washing, roughening, water washing, curing, water washing, roughening, curing, water washing, galvanizing, water washing, anti-oxidation treatment, water washing, silane, drying, and winding.

[0005] It can be seen that the copper foil production process is complicated, the process is long, the one-time investment and cost are high, and the maximum thickness of the copper foil is limited. In addition, the produced copper foil has poor impact resistance and puncture resistance. It is easy to tear after impact damage, and puncture the separator can easily cause battery short circuit and bring danger. Summary of the invention

[0006] The purpose of the present invention is to provide an ultra-thin, low-resistance conductive polymer film and a preparation method thereof, which reduces the complexity and cost of the copper foil preparation process, makes the prepared copper foil thinner and lighter, reduces the battery energy density, and gives the copper foil the impact resistance of the polymer.

[0007] To achieve the above objectives, the present invention adopts the following specific technical solutions:

[0008] An ultra-thin, low-resistance conductive polymer film, the film thickness is 2-5 μm, has no permeable pores, and has a mass resistivity of ≤0.17Ω·g / m 2 , tensile strength ≥100MPa, elongation at room temperature ≥2.5%, elongation at high temperature ≥5%, smooth surface roughness (RA) ≤0.4μm, smooth surface roughness (RZ) ≤1μm, matte surface roughness (RA) ≤0.7μm, matte surface roughness (RZ) ≤1.5μm.

[0009] Preferably, the film has a thickness of 2-3 μm, no permeable pores, and a mass resistivity of ≤0.15 Ω·g / m 2 , tensile strength ≥120MPa, elongation at room temperature ≥3%, elongation at high temperature ≥7%, smooth surface roughness (RA) ≤0.3μm, smooth surface roughness (RZ) ≤0.8μm, matte surface roughness (RA) ≤0.5μm, matte surface roughness (RZ) ≤1.2μm.

[0010] The present invention also provides a method for preparing the ultra-thin, low-resistance conductive polymer film: a polymer and an auxiliary agent are blended to form a blend, extruded through a single-layer or multi-layer die head and stretched into a film, and then electroplated through a copper sulfate solution to allow copper to further grow on the film.

[0011] Preferably, a conductive material is also added to the blend.

[0012] Furthermore, the conductive material includes nano copper powder, zinc powder, nano zinc powder, graphene, carbon black, carbon nanotubes, nano silver powder, sodium potassium alloy or gallium indium tin alloy.

[0013] Preferably, the particle size D of the conductive material is 50 The nano-conductive particles of the size are 80nm-20μm; the nano-conductive particles of the size can be well exposed on the surface of the film and are not easy to fall off the film.

[0014] Preferably, the amount of the conductive material added is 20%-50% of the mass of the polymer. An amount of conductive material added of more than 20% can make the conductive powder evenly distributed on the film, but an amount of more than 50% will cause a cliff-like loss in the strength of the polymer film.

[0015] When the conductive material includes nano copper powder or graphene, after the stretching film forming step, a conductive layer is formed on the surface of the film by vacuum ion sputtering, and then electroplating is performed using a copper sulfate solution.

[0016] When the conductive material includes zinc powder, a replacement reaction and electroplating are performed through a copper sulfate solution. That is, the zinc powder undergoes a replacement reaction in the copper sulfate solution, displacing the copper in the copper sulfate solution, so that the copper adheres to the surface of the film. The zinc powder replacement method can save the process and equipment of vacuum ion sputtering.

[0017] The extrusion molding can be a dry process or a wet process;

[0018] Preferably, no matter in the dry process or the wet process, the total stretching ratio is 2*2 times to 25*25 times.

[0019] When the extrusion molding is a dry process, the polymer includes a mixture of one or more of polypropylene, polyethylene or poly-4-methyl-1-pentene; in the polymer mixture, each component can be mixed in any proportion. Polypropylene and poly-4-methyl-1-pentene have a higher melting point, polyethylene has better elongation and flexibility, and the material blending can be compatible with a variety of material properties.

[0020] Preferably, the melt index of the polypropylene is 0.5 to 3 g / 10 min.

[0021] Preferably, the polyethylene includes one or more of HDPE, LDPE or LLDPE, and has a viscosity average molecular weight of 100,000 to 500,000.

[0022] Preferably, the melt index of the poly 4-methyl-1-pentene is 1 to 5 g / 10 min.

[0023] Preferably, in a three-layer or multi-layer system extruded through a multi-layer die, the conductive substance is not added to the middle layer, and the conductive substance is added only to the outer layer;

[0024] More preferably, when poly-4-methylpentene-1 is present in a three-layer or multi-layer system extruded through a multi-layer die, the layer containing poly-4-methylpentene-1 is extruded as an outer layer of the three-layer or multi-layer system.

[0025] In the combination, the middle layer can provide an improvement in strength, and the outer layer can provide an improvement in temperature resistance.

[0026] In the dry process, when the polymer includes poly-4-methyl-1-pentene, the working temperature during the extrusion molding is greater than 230° C.; when the polymer does not include poly-4-methyl-1-pentene, the working temperature during the extrusion molding is 140-320° C.

[0027] When the extrusion molding is a wet process, the polymer includes a mixture of one or more of polypropylene, polyethylene or poly-4-methyl-1-pentene.

[0028] Preferably, when the polymer mixture is polypropylene and polyethylene, the two are mixed in any proportion;

[0029] Preferably, when the polymer mixture is polypropylene, polyethylene and poly-4-methyl-1-pentene, the polypropylene and polyethylene are mixed in any proportion and both account for more than 60% of the solid content of the mixture;

[0030] Preferably, when the polymer mixture is polypropylene and poly-4-methyl-1-pentene, the polypropylene accounts for more than 60% of the solid content of the mixture;

[0031] Preferably, when the polymer mixture is polyethylene and poly-4-methyl-1-pentene, polyethylene accounts for more than 60% of the solid content of the mixture.

[0032] Preferably, the melt index of the polypropylene is 0.007 to 0.5 g / 10 min; or, the polypropylene is compounded with different melt indexes;

[0033] Preferably, the polyethylene includes UHMWPE or HDPE, with a viscosity average molecular weight of 500,000 to 4,000,000; or, the polyethylene is compounded with different molecular weights;

[0034] Preferably, the melt index of the poly-4-methyl-1-pentene is 0.5 to 5 g / 10 min;

[0035] Preferably, in a three-layer or multi-layer system extruded through a multi-layer die, the conductive substance is not added to the middle layer, and the conductive substance is added only to the outer layer;

[0036] More preferably, when poly-4-methylpentene-1 is present in a three-layer or multi-layer system extruded through a multi-layer die, the layer containing poly-4-methylpentene-1 is extruded as an outer layer of the three-layer or multi-layer system.

[0037] Optionally, the solvent of the wet process includes a mixture of one or more of liquid paraffin, solid paraffin, natural vegetable oil, dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, dioctyl sebacate, methyl salicylate, diphenyl ether or diphenylmethane.

[0038] In the wet process shown, when the polymer includes poly-4-methyl-1-pentene, the working temperature during extrusion molding is greater than 230°C; when the polymer does not include poly-4-methyl-1-pentene, the working temperature during extrusion molding is 140-320°C.

[0039] Further, the auxiliary agent includes one or more of a nucleating agent, an antioxidant or a polar coupling agent. Preferably, the nucleating agent includes 3988 nucleating agent, TMB-5 nucleating agent, NB-328 nucleating agent or WBG-2 nucleating agent; the antioxidant includes 1076 antioxidant, 1010 antioxidant or 168 antioxidant; the polar coupling agent includes PVDF, polyethylene glycol, adipic acid or polyvinyl alcohol.

[0040] Preferably, the total amount of the nucleating agent added is 5-10‰ of the mass of the polymer; the total amount of the antioxidant added is 7-12‰ of the mass of the polymer; the total amount of the polar coupling agent added is 5-15‰ of the mass of the polymer. During the processing or after long-term use, the polymer film will undergo oxidative degradation after ultraviolet irradiation or in oxidizing solvents, thereby reducing or losing its original function. Adding an appropriate proportion of antioxidants can effectively avoid this situation.

[0041] The conductive polymer film is used as a negative electrode current collector of a lithium battery and is superior to traditional copper foil in terms of impact resistance, puncture resistance and processing cost.

[0042] The present invention mixes a polymer with a conductive material and extrude it into a film, vacuum sputters a conductive material on the film surface to form an initial conductive layer, and then thickens the conductive layer by electroplating; or zinc powder is added to the polymer, mixed and extruded into a film, and then copper sulfate solution and zinc powder undergo a substitution reaction to form a conductive layer, and then the conductive layer is thickened by electroplating. The thickness of the polymer film can be controlled to be less than 5μm, which is thinner than conventional copper foil even after electroplating, and the polymer has impact resistance, puncture resistance and tensile properties that metals do not have. DETAILED DESCRIPTION

[0043] As used herein:

[0044] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0045] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0046] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0047] In these examples, parts and percentages are by mass unless otherwise indicated.

[0048] “And / or” is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0049] The dry process and wet process are mature processes in the prior art. The present invention is basically the same as the prior art except for the process flow and parameters specifically proposed.

[0050] Example 1

[0051] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0052] (1) The ingredients are selected as polypropylene with a melt index of 2.8g / 10min, HDPE with a molecular weight of 250,000, 3988 nucleating agent, TMB-5 nucleating agent and particle size D 50 130nm nano copper powder is used as standby. The particle size of nano copper powder is consistent with the particle size of polymer, which can achieve the effect of uniform dispersion and distribution. The smaller the particle size value, the more uniform the copper plating in the later stage.

[0053] Add polypropylene and HDPE into a powder mixing tank and mix them. The ratio of the two powders is 50% each. After mixing for 30 minutes, add 3988 nucleating agent accounting for 5‰ of the total mass of the polymer and 5‰ of TMB-5 nucleating agent. Continue stirring for 30 minutes. Then add nano copper powder accounting for 35% of the total mass of the polymer and stir and blend for 1 hour.

[0054] (2) Add the blended polymer powder, nano copper powder and two nucleating agents into a co-rotating twin screw at a processing temperature of 230° C. and a rotation speed of 120 rpm. Cool in a 15° C. water bath and extrude into granules.

[0055] (3) The granules prepared in step (2) are added into a single screw for melt plasticization extrusion at a processing temperature of 230° C. and cooled by a 15° C. chilled roller to form a cast sheet.

[0056] (4) The cooled casting is stretched 15*15 times by a bidirectional synchronous stretching machine to obtain a diaphragm with exposed copper powder on the surface.

[0057] (5) The diaphragm obtained in step (4) is subjected to vacuum ion sputtering to impart conductivity to the diaphragm.

[0058] (6) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0059] The ultra-thin, low-resistance conductive polymer film produced has a thickness of 3 μm, no permeable pores, and a mass resistivity of ≤0.15Ω·g / m 2 , tensile strength ≥120MPa, elongation at room temperature 15%, elongation at high temperature 17%, smooth surface roughness (RA) 0.3μm, smooth surface roughness (RZ) 0.8μm, matte surface roughness (RA) 0.5μm, matte surface roughness (RZ) 1.2μm.

[0060] Example 2

[0061] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0062] (1) The ingredients are selected from polypropylene with a melt index of 2.8 g / 10 min, poly-4-methyl-1-pentene with a melt index of 1.5 g / 10 min, 3988 nucleating agent, NB-328 nucleating agent, 1010 antioxidant, 168 antioxidant and particle size D 50 115nm nano zinc powder is available.

[0063] Add polypropylene and poly-4-methyl-1-pentene into a powder mixing tank and mix them. The ratio of the two powders is 50% each. After mixing for 30 minutes, add 3988 nucleating agent accounting for 5‰ of the total mass of the polymer, 5‰ of NB-328 nucleating agent, 4‰ of 1010 antioxidant and 3‰ of 168 antioxidant and continue stirring for 30 minutes. Then add nano zinc powder accounting for 35% of the total mass of the polymer and stir and blend for 1 hour.

[0064] (2) Add the blended polymer powder, nano zinc powder, nucleating agent and antioxidant into a co-rotating twin screw extruder at a processing temperature of 320° C. and a rotation speed of 120 rpm. Cool in a 15° C. water bath and extrude to form pellets.

[0065] (3) The granules prepared in step (2) are added into a single screw for melt plasticization extrusion at a processing temperature of 320° C. and cooled by a 15° C. chilled roller to form a cast sheet.

[0066] (4) The cooled casting is stretched 15*15 times by a bidirectional synchronous stretching machine to obtain a diaphragm with exposed zinc powder on the surface.

[0067] (5) The obtained bare zinc powder diaphragm is subjected to a replacement reaction with a copper sulfate solution to form a conductive layer on the surface of the diaphragm. The diaphragm is then connected to the electrode and passed through the copper sulfate solution again. The diaphragm is connected to the negative electrode and the positive electrode is placed in the copper sulfate solution to thicken the conductive layer to obtain the product.

[0068] The ultra-thin, low-resistance conductive polymer film produced has a thickness of 5 μm, no permeable pores, and a mass resistivity of 0.16 Ω·g / m 2 , tensile strength ≥120MPa, elongation at room temperature 15.3%, elongation at high temperature 25%, smooth surface roughness (RA) 0.3μm, smooth surface roughness (RZ) 1.0μm, matte surface roughness (RA) 0.5μm, matte surface roughness (RZ) ≤1.4μm.

[0069] Example 3

[0070] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0071] (1) The ingredients are polypropylene with a melt index of 0.01 g / 10 min, UHMWPE with a molecular weight of 750,000, solvent 50# paraffin oil, 3988 nucleating agent, WBG-2 nucleating agent, 1010 antioxidant, 168 antioxidant and particle size D 50 110nm nano copper powder is ready for use.

[0072] Add polypropylene and UHMWPE into a powder mixing tank and mix them. The proportion of the two powders is 12.5% ​​of the total weight of the ingredients, and the proportion of 50# paraffin oil as a solvent is 75% of the total weight of the ingredients. After the polymer and paraffin oil are mixed for 30 minutes, 5‰ of 3988 nucleating agent, 5‰ of WBG-2 nucleating agent, 8‰1010 antioxidant and 4‰168 antioxidant accounting for the total weight of the polymer are added, and stirring is continued for 2 hours. Then, nano copper powder accounting for 35% of the total weight of the polymer is added and stirred and blended for 1 hour.

[0073] (2) Add the blended polymer powder, solvent, nano copper powder, nucleating agent and antioxidant into a co-rotating twin screw extruder at a processing temperature of 140° C. and a rotation speed of 80 rpm. Cool the extruder in a 15° C. water bath to thermally induce phase separation and form a cast sheet.

[0074] (3) The cast sheet is subjected to biaxial asynchronous stretching to a stretching ratio of 20*20 times, and then passed through an extraction tank filled with dichloromethane to replace the white oil with dichloromethane to obtain a diaphragm with bare copper powder on the surface.

[0075] (4) The diaphragm obtained in step (3) is subjected to vacuum ion sputtering to impart conductivity to the diaphragm.

[0076] (5) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0077] The ultra-thin, low-resistance conductive polymer film produced has a thickness of 4 μm, no permeable pores, and a mass resistivity of ≤0.168Ω·g / m 2 , tensile strength ≥120MPa, elongation at room temperature 10%, elongation at high temperature 22%, smooth surface roughness (RA) ≤0.2μm, smooth surface roughness (RZ) 0.8μm, matte surface roughness (RA) 0.3μm, matte surface roughness (RZ) ≤1.4μm.

[0078] Example 4

[0079] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0080] (1) The ingredients are selected from poly 4-methyl 1-pentene with a melt index of 0.5 g / 10 min, UHMWPE with a molecular weight of 750,000, solvent 50# paraffin oil, TMB-5 nucleating agent, WBG-2 nucleating agent, 1010 antioxidant, 168 antioxidant and particle size D 50 300nm nano zinc powder is ready for use.

[0081] Poly (4-methyl-1-pentene) and UHMWPE were added into a powder mixing tank for blending, with the ratio of the two powders accounting for 12.5% ​​respectively, and 50# paraffin oil as a solvent accounting for 75% of the total weight of the ingredients; after the polymer and paraffin oil were mixed for 30 minutes, 5‰ of TMB-5 nucleating agent, 5‰ of WBG-2 nucleating agent, 8‰1010 antioxidant and 4‰168 antioxidant accounting for the total weight of the polymer were added, and stirring was continued for 2 hours, and then 35% of the total weight of the polymer was added and stirred for 1 hour.

[0082] (2) Add the blended polymer powder, solvent, nano zinc powder, nucleating agent and antioxidant into a co-rotating twin screw extruder at a processing temperature of 320° C. and a rotation speed of 80 rpm. Cool the extruder in a 15° C. water bath to thermally induced phase separation and form a casting sheet.

[0083] (3) The cast sheet is subjected to biaxial asynchronous stretching to a stretching ratio of 17*17 times, and then passed through an extraction tank filled with dichloromethane to replace the white oil with dichloromethane to obtain a diaphragm with zinc powder exposed on the surface.

[0084] (4) The diaphragm obtained in (3) is passed through a copper sulfate solution. The diaphragm with zinc powder on the surface undergoes a replacement reaction with the copper sulfate solution, and copper begins to grow on the surface of the diaphragm, thereby imparting conductivity to the diaphragm.

[0085] (5) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0086] The ultra-thin, low-resistance conductive polymer film produced has a thickness of 2 μm, no permeable pores, and a mass resistivity of ≤0.15Ω·g / m 2 , tensile strength ≥120MPa, elongation at room temperature 12%, elongation at high temperature 16%, smooth surface roughness (RA) 0.3μm, smooth surface roughness (RZ) 0.8μm, matte surface roughness (RA) 0.5μm, matte surface roughness (RZ) 1.2μm.

[0087] Example 5

[0088] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0089] (1) The ingredients are poly-4-methyl-1-pentene with a melt index of 0.5 g / 10 min, UHMWPE with a molecular weight of 750,000, solvent 50# paraffin oil, TMB-5 nucleating agent, WBG-2 nucleating agent, 1010 antioxidant, 168 antioxidant, polyethylene glycol and particle size D 50 For 80nm graphene spare.

[0090] Poly 4-methyl-1-pentene and UHMWPE are added to a powder mixing tank for blending, the ratio of the two powders is 12.5% ​​each, and the ratio of 50# paraffin oil as a solvent is 75% of the total weight of the ingredients; after the polymer and paraffin oil are mixed for 30 minutes, 5‰ of TMB-5 nucleating agent, 5‰ of WBG-2 nucleating agent, 8‰1010 antioxidant, 4‰168 antioxidant and 15‰ of polyethylene glycol are added to the total weight of the polymer, and stirring is continued for 2 hours, and then graphene accounting for 35% of the total weight of the polymer is added and stirred and blended for 1 hour.

[0091] (2) Add the blended polymer powder, solvent, graphene, nucleating agent, antioxidant and polar coupling agent into a co-rotating twin-screw extruder at a processing temperature of 320° C. and a rotation speed of 80 rpm. Cool the extruder in a 15° C. water bath to thermally induce phase separation and form a cast sheet.

[0092] (3) The cast sheet is subjected to biaxial asynchronous stretching to a stretching ratio of 12*12 times, and then passed through an extraction tank filled with dichloromethane to replace the white oil with dichloromethane to obtain a diaphragm with exposed graphene on the surface.

[0093] (4) The diaphragm obtained in step (3) is subjected to vacuum ion sputtering to impart conductivity to the diaphragm.

[0094] (5) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0095] The ultra-thin, low-resistance conductive polymer film produced has a thickness of 2 μm, no permeable pores, and a mass resistivity of ≤0.16Ω·g / m 2 , tensile strength ≥120MPa, elongation at room temperature 10%, elongation at high temperature 15%, smooth surface roughness (RA) 0.3μm, smooth surface roughness (RZ) 0.9μm, matte surface roughness (RA) 0.5μm, matte surface roughness (RZ) 1.2μm.

[0096] Example 6

[0097] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0098] (1) The ingredients are poly-4-methyl-1-pentene with a melt index of 0.5 g / 10 min, UHMWPE with a molecular weight of 750,000, solvent 50# paraffin oil, TMB-5 nucleating agent, WBG-2 nucleating agent, 1010 antioxidant, 168 antioxidant, PVDF and particle size D 50 A 100nm carbon nanotube is reserved.

[0099] Poly (4-methyl-1-pentene) and UHMWPE were added into a powder mixing tank for blending, with the ratio of the two powders accounting for 12.5% ​​respectively, and 50# paraffin oil as a solvent accounting for 75% of the total weight of the ingredients; after the polymer and paraffin oil were mixed for 30 minutes, 5‰ of TMB-5 nucleating agent, 5‰ of WBG-2 nucleating agent, 8‰1010 antioxidant, 4‰168 antioxidant and 10‰ of PVDF accounting for the total weight of the polymer were added, and stirring was continued for 2 hours, and then 35% of carbon nanotubes accounting for the total weight of the polymer were added and stirred for blending for 1 hour.

[0100] (2) Add the blended polymer powder, solvent, carbon nanotubes, nucleating agent, antioxidant and polar coupling agent into a co-rotating twin-screw extruder at a processing temperature of 320° C. and a rotation speed of 80 rpm. Cool the extruder in a 15° C. water bath to thermally induce phase separation and form a cast sheet.

[0101] (3) The cast sheet is subjected to biaxial asynchronous stretching to a stretching ratio of 9*9 times, and then passed through an extraction tank filled with dichloromethane to replace the white oil with dichloromethane to obtain a diaphragm with exposed carbon nanotubes on the surface.

[0102] (4) The diaphragm obtained in step (3) is subjected to vacuum ion sputtering to impart conductivity to the diaphragm.

[0103] (5) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0104] The ultra-thin, low-resistance conductive polymer film produced has a thickness of 3 μm, no permeable pores, and a mass resistivity of ≤0.15Ω·g / m 2 , tensile strength ≥ 100MPa, elongation at room temperature 11%, elongation at high temperature 15%, smooth surface roughness (RA) 0.4μm, smooth surface roughness (RZ) 0.9μm, matte surface roughness (RA) 0.7μm, matte surface roughness (RZ) 1.5μm.

[0105] Example 7

[0106] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0107] (1) The ingredients are poly-4-methyl-1-pentene with a melt index of 0.5 g / 10 min, UHMWPE with a molecular weight of 750,000, solvent 50# paraffin oil, TMB-5 nucleating agent, WBG-2 nucleating agent, 1010 antioxidant, 168 antioxidant, polyvinyl alcohol and particle size D 50 10μm nano silver powder is ready for use.

[0108] Poly 4-methyl-1-pentene and UHMWPE are added to a powder mixing tank for blending, the ratio of the two powders is 12.5% ​​each, and the ratio of 50# paraffin oil as a solvent is 75% of the total weight of the ingredients; after the polymer and paraffin oil are mixed for 30 minutes, 5‰ of TMB-5 nucleating agent, 5‰ of WBG-2 nucleating agent, 8‰1010 antioxidant, 4‰168 antioxidant and 15‰ of polyvinyl alcohol are added to account for the total weight of the polymer, and stirring is continued for 2 hours, and then 35% of nano silver powder is added to the total weight of the polymer and stirred and blended for 1 hour.

[0109] (2) Add the blended polymer powder, solvent, nano silver powder, nucleating agent, antioxidant and polar coupling agent into a co-rotating twin screw at a processing temperature of 320° C. and a rotation speed of 80 rpm. Cool in a 15° C. water bath to thermally induced phase separation and form a cast sheet.

[0110] (3) The cast sheet is subjected to biaxial asynchronous stretching to a stretching ratio of 6*6 times, and then passed through an extraction tank filled with dichloromethane to replace the white oil with dichloromethane to obtain a diaphragm with exposed nano-silver powder on the surface.

[0111] (4) The diaphragm obtained in step (3) is subjected to vacuum ion sputtering to impart conductivity to the diaphragm.

[0112] (5) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0113] The ultra-thin, low-resistance conductive polymer film produced has a thickness of 4 μm, no permeable pores, and a mass resistivity of ≤0.17 Ω·g / m 2, tensile strength ≥ 120MPa, elongation at room temperature 10%, elongation at high temperature 13%, smooth surface roughness (RA) 0.4μm, smooth surface roughness (RZ) 0.8μm, matte surface roughness (RA) 0.5μm, matte surface roughness (RZ) 1.1μm.

[0114] Example 8

[0115] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0116] (1) The ingredients are polypropylene with a melt index of 0.01 g / 10 min, UHMWPE with a molecular weight of 750,000, solvent 50# paraffin oil, 3988 nucleating agent, WBG-2 nucleating agent, 1010 antioxidant, 168 antioxidant and particle size D 50 A 110nm carbon black is reserved.

[0117] Add polypropylene and UHMWPE into a powder mixing tank and mix them. The ratio of the two powders is 12.5% ​​of the total weight of the ingredients respectively, and the ratio of 50# paraffin oil as a solvent is 75% of the total weight of the ingredients. After the polymer and paraffin oil are mixed for 30 minutes, 5‰ of 3988 nucleating agent, 5‰ of WBG-2 nucleating agent, 8‰1010 antioxidant and 4‰168 antioxidant accounting for the total weight of the polymer are added, and stirring is continued for 2 hours. Then, 35% of carbon black accounting for the total weight of the polymer is added and stirred and blended for 1 hour.

[0118] (2) Add the blended polymer powder, solvent, carbon black, nucleating agent and antioxidant into a co-rotating twin-screw extruder at a processing temperature of 140° C. and a rotation speed of 80 rpm. Cool the extruder in a 15° C. water bath to thermally induced phase separation and form a cast sheet.

[0119] (3) The cast sheet is subjected to biaxial asynchronous stretching to a stretching ratio of 20*20 times, and then passed through an extraction tank filled with dichloromethane to replace the white oil with dichloromethane to obtain a diaphragm with exposed carbon black on the surface.

[0120] (4) The diaphragm obtained in step (3) is subjected to vacuum ion sputtering to impart conductivity to the diaphragm.

[0121] (5) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0122] The ultra-thin, low-resistance conductive polymer film produced has a thickness of 3 μm, no permeable pores, and a mass resistivity of ≤0.15Ω·g / m 2, tensile strength ≥110MPa, elongation at room temperature 8%, elongation at high temperature 16%, smooth surface roughness (RA) ≤0.2μm, smooth surface roughness (RZ) 0.6μm, matte surface roughness (RA) 0.3μm, matte surface roughness (RZ) ≤1.1μm.

[0123] Example 9

[0124] The difference from Example 8 is that the conductive material is a sodium-potassium alloy.

[0125] The thickness of the conductive polymer film obtained is 2 μm, without permeable pores, and the mass resistivity is ≤ 0.12 Ω·g / m 2 , tensile strength ≥100MPa, elongation at room temperature 9%, elongation at high temperature 15%, smooth surface roughness (RA) ≤0.4μm, smooth surface roughness (RZ) 0.9μm, matte surface roughness (RA) 0.5μm, matte surface roughness (RZ) ≤1.5μm.

[0126] Example 10

[0127] The difference from Example 8 is that the conductive material is a sodium-potassium alloy.

[0128] The thickness of the conductive polymer film obtained is 2 μm, without permeable pores, and the mass resistivity is ≤ 0.13 Ω·g / m 2 , tensile strength ≥110MPa, elongation at room temperature 10%, elongation at high temperature 17%, smooth surface roughness (RA) ≤0.4μm, smooth surface roughness (RZ) 0.8μm, matte surface roughness (RA) 0.6μm, matte surface roughness (RZ) ≤1.5μm.

[0129] Embodiment 11

[0130] A method for preparing an ultra-thin, low-resistance conductive polymer film:

[0131] (1) Prepare 10 kg of polypropylene with a melt index of 2 g / 10 min, 35 kg of polyethylene compounded with molecular weights of 250,000 and 1.4 million, 5 kg of polyethylene / propylene copolymer, 48.5 kg of liquid paraffin, 1 kg of adipic acid and 0.5 kg of 1076 antioxidant, stir for 2 h to form a mixed suspension as the formula for the middle layer.

[0132] (2) Prepare 25 kg of polypropylene with a melt index of 2 g / 10 min, 6 kg of polyethylene compounded with molecular weights of 250,000 and 1.4 million, 6 kg of polyethylene / propylene copolymer, 67.5 kg of liquid paraffin, 1 kg of adipic acid and 0.5 kg of 1076 antioxidant, stir for 2 h, then add 35% of nano copper powder of the main material and stir and blend for 1 h to form a blended suspension as the formula for the outer layer.

[0133] (3) Two co-rotating twin screws are connected in parallel to plasticize the above-mentioned blending systems with different formulations, and a three-layer die is used to compositely and synchronously extrude the blending systems with different formulations in the die to obtain cast sheets. The feeding method is synchronous feeding, the screw temperature is 140°C-220°C, the melt pipe temperature is 190°C, the die temperature is 190°C, and the melt thickness is 2 mm.

[0134] (4) During the post-treatment process, the cooling method is chilled roller and water cooling at 25°C, and the melt drawing speed ratio is 1.8. The stretching conditions and methods are: 140°C wind temperature, 120°C film surface temperature, 10mm / s stretching speed, and bidirectional synchronous stretching of 15*15 times. After passing through an extraction tank filled with dichloromethane, the white oil is replaced into dichloromethane to obtain a diaphragm with exposed copper powder on the surface.

[0135] (5) The separator obtained in (4) is subjected to vacuum ion sputtering to impart conductivity to the separator.

[0136] (6) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0137] The thickness of the obtained conductive polymer film is 4 μm, without permeable pores, and the mass resistivity is ≤ 0.13 Ω·g / m 2 , tensile strength ≥180MPa, elongation at room temperature 10%, elongation at high temperature 18%, smooth surface roughness (RA) ≤0.4μm, smooth surface roughness (RZ) 0.8μm, matte surface roughness (RA) 0.6μm, matte surface roughness (RZ) ≤1.5μm.

[0138] Example 12

[0139] (1) Prepare 10 kg of 600,000 molecular weight polyethylene, 35 kg of polyethylene compounded with 250,000 and 1.4 million molecular weight polyethylene, 5 kg of polyethylene / propylene copolymer, 48.5 kg of liquid paraffin, 1 kg of adipic acid and 0.5 kg of 1076 antioxidant, stir for 2 hours to form a mixed suspension as the formula for the middle layer.

[0140] (2) Prepare 25 kg of polypropylene with a melt index of 2 g / 10 min and 6 kg of polypropylene with a melt index of 0.01 g / 10 min, 6 kg of polyethylene / propylene copolymer, 67.5 kg of liquid paraffin, 1 kg of adipic acid and 0.5 kg of 1076 antioxidant, stir for 2 hours, then add 35% of nano copper powder of the main material powder and stir and blend for 1 hour to form a blended suspension as the formula for the outer layer.

[0141] (3) Two co-rotating twin screws are connected in parallel to plasticize the above-mentioned blending systems with different formulations, and a three-layer die is used to compositely and synchronously extrude the blending systems with different formulations in the die to obtain cast sheets. The feeding method is synchronous feeding, the screw temperature is 140°C-220°C, the melt pipe temperature is 190°C, the die temperature is 190°C, and the melt thickness is 3 mm.

[0142] (4) During the post-treatment process, the cooling method is chilled roller and water cooling at 25°C, and the melt drawing speed ratio is 1.8. The stretching conditions and methods are: 140°C wind temperature, 120°C film surface temperature, 10mm / s stretching speed, and bidirectional synchronous stretching 20*20 times. After passing through an extraction tank filled with dichloromethane, the white oil is replaced into dichloromethane to obtain a diaphragm with exposed copper powder on the surface.

[0143] (5) The separator obtained in (4) is subjected to vacuum ion sputtering to impart conductivity to the separator.

[0144] (6) The obtained conductive diaphragm is electroplated with copper in a copper sulfate solution, the diaphragm is connected to the negative electrode, the positive electrode is placed in the copper sulfate solution, the conductive layer is thickened, and the product is obtained.

[0145] The thickness of the obtained conductive polymer film is 5 μm, without permeable pores, and the mass resistivity is ≤ 0.13 Ω·g / m 2 , tensile strength ≥190MPa, elongation at room temperature 10%, elongation at high temperature 20%, smooth surface roughness (RA) ≤0.4μm, smooth surface roughness (RZ) 0.8μm, matte surface roughness (RA) 0.6μm, matte surface roughness (RZ) ≤1.5μm.

[0146] Comparative Examples 1 and 2 are both copper foils, and the copper foil of Comparative Example 2 is thicker.

[0147] The product indicators obtained in Examples 2-3 and Comparative Examples 1-2 are now compared, see Table 1.

[0148]

[0149]

[0150] Although the product indicators in Example 2 are not much different from those in Example 3, the process and equipment of vacuum ion sputtering are omitted, which greatly reduces the one-time investment cost and production cost.

[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

[0152] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present invention and to form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present invention and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. An ultra-thin, low-resistance conductive polymer film, characterized in that: The film has a thickness of 2-5 µm, has no permeable pores, and a mass resistivity of ≤0.17 Ω·g / m 2 , tensile strength ≥ 100MPa, elongation at room temperature ≥ 2.5%, elongation at high temperature ≥ 5%, smooth surface roughness RA ≤ 0.4μm, smooth surface roughness RZ ≤ 1μm, matte surface roughness RA ≤ 0.7μm, matte surface roughness RZ ≤ 1.5μm; The preparation method of the conductive polymer film comprises: blending a polymer and an auxiliary agent to form a blend, extruding and stretching the blend through a single-layer or multi-layer die head to form a film, and then electroplating the blend through a copper sulfate solution to further grow copper on the film. Wherein, a conductive material is also added to the blend, and the amount of the conductive material added accounts for 20%-50% of the mass of the polymer; When the extrusion molding is a dry process, the polymer includes a mixture of one or more of polypropylene, polyethylene or poly-4-methyl-1-pentene; When the extrusion molding is a wet process, the polymer includes a mixture of one or more of polypropylene, polyethylene, polyethylene / propylene copolymer or poly-4-methyl-1-pentene; The auxiliary agent includes one or more of a nucleating agent, an antioxidant or a polar coupling agent.

2. A method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 1, characterized in that: The polymer and the auxiliary agent are mixed to form a blend, a conductive material is added to the blend, and the blend is extruded through a single-layer or multi-layer die head and stretched into a film, and then electroplated through a copper sulfate solution to further grow copper on the film, thereby obtaining; The added amount of the conductive material accounts for 20%-50% of the mass of the polymer.

3. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 2, characterized in that: The conductive material includes nano copper powder, zinc powder, graphene, carbon black, carbon nanotubes, nano silver powder, sodium potassium alloy or gallium indium tin alloy.

4. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 3, characterized in that: The particle size D of the conductive material 50 80 nm-20μm.

5. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 3, characterized in that: When the conductive material includes nano copper powder or graphene, after the stretching film forming step, a conductive layer is formed on the film surface by ion sputtering, and then electroplating is performed by copper sulfate solution.

6. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 3, characterized in that: When the conductive material includes zinc powder, a replacement reaction and electroplating are performed by using a copper sulfate solution.

7. The method for preparing an ultra-thin, low-resistance conductive polymer film according to any one of claims 2 to 6, characterized in that: The extrusion molding is a dry process or a wet process; In the dry process or the wet process, the total stretching ratio is 2*2 times to 25*25 times.

8. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 7, characterized in that: When the extrusion molding is a dry process, the polymer includes a mixture of one or more of polypropylene, polyethylene or poly-4-methyl-1-pentene, and the components in the polymer mixture are mixed in any proportion.

9. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 8, characterized in that: The melt index of the polypropylene is 0.5-3 g / 10min.

10. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 8, characterized in that: The polyethylene includes one or more of HDPE, LDPE or LLDPE, and has a viscosity average molecular weight of 100,000 to 500,000.

11. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 8, characterized in that: The melt index of the poly 4-methyl-1-pentene is 1-5 g / 10min.

12. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 8, characterized in that: In a three-layer or multi-layer system extruded through a multi-layer die, the conductive substance is not added to the middle layer, and only to the outer layer.

13. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 12, characterized in that: When poly-4-methylpentene-1 is present in a three-layer or multi-layer system extruded through a multi-layer die, the layer containing poly-4-methylpentene-1 is extruded as an outer layer of the three-layer or multi-layer system.

14. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 7, characterized in that: When the extrusion molding is a wet process, the polymer includes a mixture of one or more of polypropylene, polyethylene, polyethylene / propylene copolymer or poly-4-methyl-1-pentene.

15. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: The melting index of the polypropylene is 0.007-0.5 g / 10min; or, the polypropylene is compounded with different melting indexes.

16. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: The polyethylene includes UHMWPE or HDPE, with a viscosity average molecular weight of 500,000 to 4,000,000; or, the polyethylene is compounded with different molecular weights.

17. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: The melt index of the poly 4-methyl-1-pentene is 0.5-5 g / 10min.

18. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: The solvent of the wet process includes a mixture of one or more of liquid paraffin, solid paraffin, natural vegetable oil, dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, dioctyl sebacate, methyl salicylate, diphenyl ether or diphenylmethane.

19. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: When the polymer mixture is polypropylene and polyethylene, the two can be mixed in any ratio.

20. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: When the polymer mixture is polypropylene, polyethylene and poly-4-methyl-1-pentene, the polypropylene and polyethylene are mixed in any proportion and the two account for more than 60% of the solid content of the mixture.

21. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: When the polymer mixture is polypropylene and poly-4-methyl-1-pentene, the polypropylene accounts for more than 60% of the solid content of the mixture.

22. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: When the polymer mixture is polyethylene and poly-4-methyl-1-pentene, polyethylene accounts for more than 60% of the solid content of the mixture.

23. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 14, characterized in that: In a three-layer or multi-layer system extruded through a multi-layer die, the conductive substance is not added to the middle layer, and only to the outer layer.

24. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 23, characterized in that: When poly-4-methylpentene-1 is present in a three-layer or multi-layer system extruded through a multi-layer die, the layer containing poly-4-methylpentene-1 is extruded as an outer layer of the three-layer or multi-layer system.

25. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 8 or 14, characterized in that: When the polymer includes poly-4-methyl-1-pentene, the working temperature during the extrusion molding is greater than 230° C.; When the polymer does not include poly-4-methyl-1-pentene, the working temperature during the extrusion molding is 140-320°C.

26. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 7, characterized in that: The auxiliary agent includes one or more of a nucleating agent, an antioxidant or a polar coupling agent.

27. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 26, characterized in that: The nucleating agent includes 3988 nucleating agent, TMB-5 nucleating agent, NB-328 nucleating agent or WBG-2 nucleating agent; the antioxidant includes 1076 antioxidant, 1010 antioxidant or 168 antioxidant; the polar coupling agent includes PVDF, polyethylene glycol, adipic acid or polyvinyl alcohol.

28. The method for preparing an ultra-thin, low-resistance conductive polymer film according to claim 26, characterized in that: The total amount of the nucleating agent added accounts for 5-10‰ of the mass of the polymer; the total amount of the antioxidant added accounts for 7-12‰ of the mass of the polymer; and the total amount of the polar coupling agent added accounts for 5-15‰ of the mass of the polymer.

Citation Information

Patent Citations

  • Lithium battery by using lightweight current collector

    CN111129505A

  • High-performance thermal radiation heat dissipation copper foil material

    CN114059132A